Нетрадиційні види сировини для спиртового виробництва - Левандовський, Леонід Вікторович; Олійнічук, Сергій Тимофійович; Ткаченко, Любов Володимирівна (My University, 2011)
Наведено склад соризу та насіння амаранту і показано можливість переробки цієї сировини в спирт. Визначено ефективні режими для перероблювання соризу та насіння амаранту за різними схемами розварювання. Встановлено вихід спирту з 1 т переробленої сировини (соризу та насіння амаранту). The composition of soriz and seeds of Amaranthus is derived and the possibility of its processing into ethyl alcohol is demonstrated. Effective regimes for the processing of soriz and seeds of Amaranthus according to various schemes of cooking are presented. The alcohol outcome of 1 ton of raw material (soriz and seeds of Amaranthus) is determined.
Keywords: сориз; зброджування; дозріла бражка; насіння амаранту; спирт; soriz; seeds of Amaranthus; alcohol; fermentation; fermented mash